PENINGKATAN HASIL BELAJAR LEMPAR TANGKAP SISWA SEKOLAH DASAR DENGAN MODIFIKASI PERMAINAN BEREGU (Department of Physical Education, Sport, Health and Recreation, 2014)
This study aims to improve learning outcomes throwing catch on third-grade students of SDN 03 BatangPurbo. Modification used is Team game. Results showed that pre-cycle mastery learning the material caughtthrowing KKM is less than 70 it is in tujukkan of results pre-cycle value is the average value of 60 and onlyachieve mastery 28% of the total number of students is 14. Having applied the method on a cycle Team game1, an increase in the average value is 73 and the completeness reaches 64% of the total number of students thatmeet the initial target completeness 14.untuk 100% then proceed to cycle 2 to further enhance students' masterylearning while using a modification of the game Team completeness result 86 % and the average score ofstudents to 84. Conclusions This study suggests that modification Team games can improve learning outcomesthrowing catch on third-grade students of SDN Purbo 03.